Highly active and stable Co (Co3O4)_Sm2O3 nano-crystallites derived from Sm2Co7 and SmCo5 intermetallic compounds in NH3 synthesis and CO2 conversion. Issue 2 (21st December 2021) - Marakatti, Vijaykumar S.; Ronda-Lloret, Maria; Krajčí, Marian; Joseph, Boby; Marini, Carlo; Delgado, Juan Jose; Devred, François; Shiju, N. Raveendran; Gaigneaux, Eric M.
Abstract : Structural and electronic properties of Sm2 Co7 and SmCo5 Intermetallic compound derived catalysts in activation of N2 and CO2 molecules. Abstract : Intermetallic compounds (IMCs) are interesting materials in the field of heterogeneous catalysis due to their ordered structure and tunable electronic properties. These IMCs can act as precursor to synthesize metal/metal oxide composite catalysts that are more active than just the starting IMCs. In this work, Sm2 Co7 and SmCo5 IMCs were used as precursors to prepare highly active and stable Co_SmO, Co_Sm2 O3 and Co3 O4 _Sm2 O3 catalysts via controlled modification. Transmission electron microscopy (TEM) demonstrated that Co and Sm2 O3 Nano crystallites were formed after the modification of the IMC. IMCs derived Co_SmO and Co_Sm2 O3 were stable and active in NH3 synthesis with very low activation energy of 55 and 77 kJ mol −1 respectively. The structural, morphological and surface characterization revealed that a strong metal support interaction existed between Co and Sm2 O3 (electronic effect) along with the presence of surface steps and edges of Co nano crystallites (structural effect) that activate the N2 at low temperature (360 °C). Similarly, Co3 O4 _Sm2 O3 derived from the IMC were found to exhibit high CO2 and butane conversion in butane dry reforming at low temperature (550 °C) with excellent stability. The study revealed that the presence of Co3 O4 and Sm2 O3 active sites in close proximity (geometrical effect) promoted the simultaneous adsorption or activation of butane and CO2 . The Co_Sm2 O3 and Co3 O4 _Sm2 O3 derived from IMCs exhibited superior catalytic performance in both NH3 synthesis and butane dry reforming compared to similar compositional catalyst synthesized by hydrothermal route. These studies pave the way to potential uses of IMCs as precursors to derive composite metal/metal oxide catalysts that are highly stable and active despite their low surface areas.